Social Responsibility and Entrepreneurship in Organizations Dedicated to the Provision of Social Services: Case Studies in the Region of Murcia, Spain - Pérez Daruiz, María Teresa; Briones Peñalver, Antonio Juan (Cooperativismo & Desarrollo, 2014)
Organizations dedicated to social services provision acquire increasingly greater importance in all countries. Such entities propose alternative models for society with innovative proposals aimed at reducing social gaps in the cause of peace. They are promoted by governments and adapted for enterprises, using values supported by management theories based on responsibility. This work reviews the character of social enterprises along with their good practices in organizations with social activities while comparing them with the dimensions of social responsibility. It involves a study of multiple cases at nonprofit organizations with respect to academic indicators that were also proposed by experts or social agents, specifically looking at three cases: associations, special centers for employment, and insertion companies in the Region of Murcia (Spain). The research deals with the organizations while analyzing hypotheses about dependent associations and providing statistical results for their characterization.
Keywords: entrepreneur; social entrepreneur; nonprofit organizations (npo); social responsibility.